4-Methoxy-phenyl 2,3,4,6-tetra-O-acetyl-1-thio-α-d-mannopyran-oside. - Drouin, L; Cowley, A; Fairbanks, A; Thompson, A (2008)
The title compound, C(21)H(26)O(10)S, was synthesized in a single step from mannose penta-acetate. The mol-ecular structure confirms the α configuration of the anomeric thioaryl substituent. Spectroscopic and melting-point data obtained for the title compound are in disagreement with those previously reported, indicating the previously reported synthesis [Durette and Shen (1980 ▶). Carbohydr. Res. 81, 261-274] to be erroneous. The crystal structure is stabilized by weak inter-molecular C-H⋯O hydrogen bonds.